Decision-making by the NICE Interventional Procedures Advisory Committee. Issue 13 (25th October 2019) - Carroll, C; Dickson, R; Boland, A; Houten, R; Walton, M
Abstract: Background: This study explored the evidence base for recommendations by the National Institute of Health and Care Excellence (NICE) Interventional Procedures Advisory Committee, the only NICE committee not to consider cost. The four potential recommendations are: Standard Arrangements (can be performed as routine practice in the NHS); Special Arrangements (can be done under certain conditions); Research Only; and Do Not Do. Methods: Quantitative content analysis of data extracted from all published Interventional Procedure Guidance (IPG) for 2003–2018 ( n = 496) was undertaken. All data were extracted independently by two researchers; disagreements were clarified by consensus. Data were tabulated, descriptive statistics produced, and regression analyses performed. Results: The proportion of IPGs by recommendation was: 50·0 per cent Standard Arrangements; 37·2 per cent Special Arrangements; 11·1 per cent Research Only; and 1·6 per cent Do Not Do. There was a clear trend over time: the proportion of recommendations for Standard Arrangements decreased, whereas the evidence threshold increased. Adjusted mean numbers of patients in the evidence base by recommendation type were: Standard, 4867; Special, 709; Research Only, 386. Regression analyses confirmed that the year of recommendation, numbers of patients and levels of evidence all affected the likely recommendation. Conclusion: This study suggests that the likelihood of achieving the most positive recommendation (Standard Arrangements) is decreasing, and that this is most likely due to evidential requirements becoming more demanding. These findings are distinct from those reported for other NICE committees, for which the cost and statistical superiority of new therapies are among the drivers of recommendations. Graphical Abstract: The likelihood of a procedure receiving the most positive recommendation from the NICE Interventional Procedures Advisory Committee has decreased over time, while evidence requirements have increased. How NICE works